IMPLEMENTASI PENGEMBANGAN PENDIDIKAN MULTIKULTURAL DI SEKOLAH - Mohamad Solihin; Muhammad Hendra Firmansyah (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
The current education situation in Indonesia is no longer adequate for people who havediverse and more than one culture. Therefore, change or transformation is needed in theeducation domain in Indonesia, by adopting the concept of multicultural education as analternative to education that only follows one culture.The importance of multicultural education has received a positive response in several casesand is strengthened by Law of the Republic of Indonesia no. 20 of 2003 concerning theNational Education System. This law includes human rights values as an integral part of thenational education system, upholds the principles of justice, and emphasizes the importanceof respecting human rights, religious values, cultural values, and the nation's culturaldiversity.So, the implementation of education requires and requires a curriculum that hasmulticultural values. These values must be the main basis for planning, implementing andevaluating curricula in various educational institutions, including schools, madrasas andIslamic boarding schools. Islamic religious education also has an important role in instillingthe values of multiculturalism in students, which are based on the teachings of the Koranand hadith. This teaching has the potential to form students who have faith in God Almighty.Apart from that, the aim of implementation and values in learning Islamic religious educationis to help students develop knowledge and behavior both in individual and social life.